Significance of international law in legal research: A Third World approach to the transferability of international legal standards to domestic contexts - Seneviratne, W.; Thilakarathna, K.A.A.N. (University of Colombo, 2025)
This paper critically interrogates the fraught and often asymmetrical relationship between international law and domestic legal research through the analytical lens of Third World Approaches to International Law (TWAIL). It explores how international legal standards and norms are transferred, selectively adapted, or outright contested within the legal systems of postcolonial states, where the legacies of imperialism continue to shape institutional, epistemic, and normative landscapes. By grounding the inquiry in TWAIL’s four central critiques, historical, structural, epistemic, and emancipatory, which collectively expose the deep-rooted inequalities and hegemonic biases embedded in the international legal order this study challenges the presumed universality, neutrality, and legitimacy of international legal norms. Through a methodology that combines critical discourse analysis, multi-sited ethnography, and decolonial research strategies, the paper analyzes case studies from Sri Lanka and India to reveal how embedding of international legal standards often fails to resonate with local legal imaginaries and social realities. The findings emphasize that such legal transfers are not merely technical acts of compliance or reform, but politically loaded processes that risk reproducing colonial hierarchies under the guise of universality and modernization...
Keywords: Third World Approaches to International Law; Legal hybridization; Postcolonial legal systems; International norm transfer